Application of fiber bragg grating sensors in monitoring civil engineering structures - Chin, Kai San (2006)
Fiber Bragg grating (FBG) is finding increasing usage in aerospace guidance, marine structures and civil engineering applications. This is due to their lightweight, non-obtrusive, immunity to electromagnetic interference, high bandwidth and sensitivity, and solid-state properties. Analysis of case studies is carried out to study the applications of Fiber Bragg grating sensors in civil engineering structures. In this research, a fiber Bragg grating sensing system for strain measurement is being described. Low cost and simple grating-based FBG has been used to produce the strain and induce Bragg wavelength shifts. A brief experimental testing on an instrumented metal plate showed that the proposed system is able to perform strain measurements with linear response. A general guideline is proposed on the fabrication and installation of fiber Bragg gratings for structural monitoring in local conditions.